2021
DOI: 10.3389/fpls.2021.798230
|View full text |Cite
|
Sign up to set email alerts
|

Plant Immune Memory in Systemic Tissue Does Not Involve Changes in Rapid Calcium Signaling

Abstract: Upon pathogen recognition, a transient rise in cytoplasmic calcium levels is one of the earliest events in plants and a prerequisite for defense initiation and signal propagation from a local site to systemic plant tissues. However, it is unclear if calcium signaling differs in the context of priming: Do plants exposed to a first pathogen stimulus and have consequently established systemic acquired resistance (SAR) display altered calcium responses to a second pathogen stimulus? Several calcium indicator syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Lines of about equally low CPK5 protein levels were selected by western blot to allow a comparison of the T98 substitution. This is of particular importance because we have demonstrated that the protein amount of active CPK5 enzyme may result in enhanced CPK5 signaling influencing the degree of defense responses from as early as Ca 2+ signature (55) to defense gene expression and resistance to bacterial pathogen Pto DC 3000 (12). A smaller rosette size in 6 weeks-old plants was observed upon expression of CPK5-YFP compared to the cpk5 parental line, which is even further reduced in the T98A variant but not in the T98D variant (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lines of about equally low CPK5 protein levels were selected by western blot to allow a comparison of the T98 substitution. This is of particular importance because we have demonstrated that the protein amount of active CPK5 enzyme may result in enhanced CPK5 signaling influencing the degree of defense responses from as early as Ca 2+ signature (55) to defense gene expression and resistance to bacterial pathogen Pto DC 3000 (12). A smaller rosette size in 6 weeks-old plants was observed upon expression of CPK5-YFP compared to the cpk5 parental line, which is even further reduced in the T98A variant but not in the T98D variant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CPK5 becomes biochemically activated within sec to min upon pathogen perception and functions as signaling hub in the control of the plant immune response. In local immunity enhanced CPK5 signaling in CPK5-YFP overexpressing lines leads to an enforcement of the cytoplasmic Ca 2+ signature (55), ROS generation, defense gene expression and pathogen resistance (12). Furthermore, CPK5 contributes to post-invasive immunity during the onset and maintenance of systemic acquired resistance in the entire plant (12, 16, 19).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged Ca 2+ influx and intermediate oscillation are observed in systemic response in plants (Aldon et al, 2018). Instead, recently, it was observed that in response to flg22, systemic tissue does not impose rapid induction of calcium oscillation but rather calcium-dependent downstream signalling instigated in Arabidopsis thaliana (Eichstädt et al, 2021). Uncontrolled production of calcium, overactivation of calcium channels, or autoregulated calcium influx may negatively affect the plant immune system and cause inappropriate defence response.…”
Section: Plant-microbe Interaction: a Needle In A Haystackmentioning
confidence: 99%
“…For epidermal peal sample preparation leaf material from 2 -3 week old plants grown on jiffy-7 soil (Jiffy Products) under short-day conditions (10 h day light, 20 -22°C; 60 % RH) were used. Epidermal peel sample preparation in 2 well chambered coverslips (IBIDI) has been described in detail (Eichstädt et al, 2021). Fresh prepared epidermis single-layer was directly immersed with 1 ml plant buffer (10 mM MES-Tris pH 6. occurring in some guard cells were discussed elsewhere (Allen et al, 1999;Klüsener et al, 2002;Hubbard et al, 2012).…”
Section: Live-cell Fluorescence Imaging In Guard Cellmentioning
confidence: 99%
“…Ca 2+ signatures are defined through magnitude, number, duration and location of Ca 2+ transients and are generated by the coordinated actions of Ca 2+ channels and transporter (Yuan et al, 2014; Toyota et al, 2018; Tian et al, 2019; Thor et al, 2020; Tian et al, 2020; Bjornson et al, 2021; Köster et al, 2022; Xu et al, 2022). With respect to Ca 2+ encoding major achievements in Ca 2+ imaging have led to an increasing knowledge of real time Ca 2+ dynamics in combination with Ca 2+ permeable channel activities (Thor and Peiter, 2014; Toyota et al, 2018; Huang et al, 2019; Tian et al, 2019; Mou et al, 2020; Thor et al, 2020; Waadt et al, 2020; Bi et al, 2021; Bjornson et al, 2021; Eichstädt et al, 2021; Li et al, 2021; Guo et al, 2022; Tan et al, 2022; Xu et al, 2022). Yet, the Ca 2+ decoding step, and in particular its assessment in real-time in living cells, remains a major challenge.…”
Section: Introductionmentioning
confidence: 99%